MAKSUD SHEIKHZADA IS A GREAT TRANSLATOR - Sodikova , Robiya Dilshod kizi (Educational Research in Universal Sciences, 2023)
The article talks about Maksud Sheikhzada, who created a great school of translation. Although this great man hailed from Azerbaijan, he left an indelible mark on Uzbek literature in terms of translation, drama and poetry. Also, it will be discussed which rare works of world literature he chose and skilfully translated, and which aspects of rare works of world classics were presented to the Uzbek people in the translation of the poet and dramatist Sheikhzoda. Obviously, I am incapable of analyzing the work of this artist who served in Uzbekistan, rich in deep ideas and great skills, but I found it necessary to talk about them due to my love for the poet’s unique generous spiritual world and unique great talent.